If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1 = 15 * -55 Reorder the terms: -1 + 6x = 15 * -55 Multiply 15 * -55 -1 + 6x = -825 Solving -1 + 6x = -825 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 6x = -825 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = -825 + 1 6x = -825 + 1 Combine like terms: -825 + 1 = -824 6x = -824 Divide each side by '6'. x = -137.3333333 Simplifying x = -137.3333333
| 4(4.5+2.5)-2y=5 | | 19x-6=6(x+3)-10 | | 2xy+4x-y=4 | | 4(9x+2)=153 | | P=-2b-3t-2t+b | | 46x-45x=1 | | 2w+30=60-x | | T=3a-4b+2a+b | | 3x-11=ax+6 | | x^2/3-11x/6-1=0 | | 10t-3=24 | | a/9=15 | | X-7x+6=30 | | 0=x+4-9x | | 2.6=-5.2(3.4+x) | | 0.1x=1.4 | | 34=-0.4(x+22) | | -0.26=logx | | -4(-5-b)= | | 3(x-9)=6(x+3) | | sinx=-0.95 | | 10x+15x-8+3=-2x+3-8 | | 7p-8=-3p+6 | | 2=4y-2y-6 | | 6e-15=15 | | x+37=3x+9 | | (x-8)+23-4=36 | | 42=28-3c | | 5k+26=1 | | -3e^1-x=11 | | (-r^2)+4(-r)-4=-8 | | 6-c=3 |